2016
DOI: 10.1093/glycob/cww019
|View full text |Cite
|
Sign up to set email alerts
|

Hexosamine biosynthesis in keratinocytes: roles of GFAT and GNPDA enzymes in the maintenance of UDP-GlcNAc content and hyaluronan synthesis

Abstract: UDP-N-acetylglucosamine (UDP-GlcNAc) is a glucose metabolite with pivotal functions as a key substrate for the synthesis of glycoconjugates like hyaluronan, and as a metabolic sensor that controls cell functions through O-GlcNAc modification of intracellular proteins. However, little is known about the regulation of hexosamine biosynthesis that controls UDP-GlcNAc content. Four enzymes can catalyze the crucial starting point of the pathway, conversion of fructose-6-phosphate (Fru6P) to glucosamine-6-phosphate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 48 publications
1
33
0
Order By: Relevance
“…Therefore, our results concerning strong down-regulation of COL6A1 gene expression in glioma cells upon inhibition of IRE1 completely agree with the functional role of this protein in tumor cells and with suppression of IRE1 knockdown glioma cell proliferation [7,22]. We have also shown that the expression of DEK, HOMER3, and GNPDA1 genes is downregulated and these results agree well with data concerning the functional role of DEK, HOMER3, and GNPDA1 proteins encoding by these genes [25][26][27]. Thus, DEK induces cell proliferation and its expression is required for tumorigenesis [25]; HOMER3 is overexpressed in some cancers [26], and GNPDA1 enhances cell proliferation through the synthesis of glycoconjugates and modification of intracellular proteins [27].…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Therefore, our results concerning strong down-regulation of COL6A1 gene expression in glioma cells upon inhibition of IRE1 completely agree with the functional role of this protein in tumor cells and with suppression of IRE1 knockdown glioma cell proliferation [7,22]. We have also shown that the expression of DEK, HOMER3, and GNPDA1 genes is downregulated and these results agree well with data concerning the functional role of DEK, HOMER3, and GNPDA1 proteins encoding by these genes [25][26][27]. Thus, DEK induces cell proliferation and its expression is required for tumorigenesis [25]; HOMER3 is overexpressed in some cancers [26], and GNPDA1 enhances cell proliferation through the synthesis of glycoconjugates and modification of intracellular proteins [27].…”
Section: Resultssupporting
confidence: 89%
“…The suppression level of IRE1 and enzymatic activity in glioma cells that overexpress a dominantnegative construct of inositol requiring enzyme-1 was estimated previously [27,28] by determining the phosphorylation of IRE1 and the expression level of XBP1 alternative splice variant (XBP1s), a key transcription factor in IRE1 signaling, using cells treated by tunicamycin (0.01 mg/ml during 2 h). Moreover, the proliferation rate of glioma cells with mutated IRE1 is decreased 2 times [28].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been well recognized that changes in traditional N- and O-linked glycosylation is correlated with oncogenesis25. In addition, UDP-GlcNAc is also used as the substrate for O -linked β-N-actylglucosamine modification ( O -GlcNAcylation) on nucleocytoplasmic and mitochondrial proteins26. Hyper- O -GlcNAcylation was found in multiple types of human malignancies, and considered as a general feature of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Enzymatic antioxidant of GST converts reactive electrophilic species to hydrophilic forms then are conjugated by GSH and easily excreted. Non-enzymatic antioxidants like vitamins C and E and lipoic acid are involved in the termination of the lipid peroxidation process (13,14). …”
Section: Diabetic Kidney Diseasementioning
confidence: 99%